RESEARCH AND DEVELOPMENT OF DIODE-PUMPED PASSIVELY Q-SWITCHED Nd:YVO4 LASERS USING Cr4+:YAG CRYSTAL AS SATURABLE ABSORBER - Nguyen Trong Nghia; Trinh Dinh Huy; Le Thi Thanh Nga; Nguyen Dai Hung (Universitas Gadjah Mada, 2007)
The results in research and development of diode-pumped passively Q-switched Nd:YVO4 lasers are presented with Cr4+:YAG crystal used as an intra-cavity saturable absorber. Using a-cut Nd:YVO4 laser crystals, the passively Q-switched lasers have been successfully developed and provided stable single shortest pulses of 40 ns at the repetition rate of 18.5 kHz, the maximal average output power of 180 mW was achieved corresponding to the optical efficiency of 9% and the slope efficiency of 16%. The dependences of average output power, repetition rate, pulse width and peak power on pump diode power for different transmissions of output mirror are also investigated.